Structure-Reactivity Correlation in the Oxidation of Substituted Benzaldehydes by Tetraethylammonium Chlorochromate - Gehlot, M.; Prasadrao, P.T.S.R.K.; Sharma, V. (Asian Journal of Chemistry, 2010)
Oxidation of 36 monosubstituted benzaldehydes by tetraethylammonium chlorochromate in dimethyl sulphoxide, leads to the formation of corresponding benzoic acids. The reaction is of first order with respect to chlorochromate and aldehydes. The reaction is promoted by H+; the H+ dependence has the form kobs = a + b[H+]. The oxidation of duteriated benzaldehyde exhibits substantial primary kinetic isotope effect. The reaction was studied in 19 different organic solvents and the effect of solvent was analyzed using Taft's and Swain's multi-parametric equations. The rates of the oxidation of para- and meta-substituted benzaldehydes showed excellent correlation in terms of Charton's triparametric LDR equation, whereas the oxidation of ortho-substituted benzaldehydes were correlated well with tetraperametric LDRS equation. The oxidation of parasubstituted benzaldehydes is more susceptible to the delocalized effect than is the oxidation of ortho- and meta- substituted compounds, which display a greater dependence on the field effect. The positive value of η suggests the presence of an electron-deficient reaction centre in the ratedetermining step. The reaction is subjected to steric acceleration by the ortho-substituents. A suitable mechanism has been proposed.